Gender-Based Violence and Negative Outcomes in Post-Primary Educational Institutions: Implications for Strategic Leadership Engagements - Olusolami Bamidele OKUNLOLA; Abiodun Matthew GESINDE; Adedayo Jonathan; ODUKOYA; Gbadebo Olubunmi ADEJUMO (Communications of International Proceedings, 2020)
Gender-based violence (GBV) is a 21st century reality across all nations of the world. GBV is observed to present various long and short term negative outcomes in women and girls especially. These outcomes could be educational, social, physical or/and psychological consequences, including low self-esteem. Low self-esteem tends to hamper adolescents’ academic motivation and psychological wellbeing. This study investigated the self-esteem outcomes of GBV among adolescent girls in post-primary schools across Lagos, Nigeria. The design adopted for the study was descriptive survey using multistage sampling technique to enlist a total of 588 sexually abused and 576 non-sexually abused female adolescents from three educational districts of Lagos State. The Rosenberg Self-esteem Scale (RSES) and Child Sexual Abuse Questionnaire (CSAQ) were used to obtain data. The results indicate that female adolescents who had experienced GBV in form of sexual abuse reported lower self-esteem levels than their non-sexually abused counterparts. The implications of the findings for strategic leadership engagements at home, school, community and national levels were discussed.
Keywords: Gender-based violence; sexual abuse; self-esteem; secondary school adolescents.